2019
DOI: 10.1016/j.jtho.2019.08.514
|View full text |Cite
|
Sign up to set email alerts
|

MA03.05 BRAF Mutations Are Associated with Increased Benefit from PD1/PDL1 Blockade Compared with Other Oncogenic Drivers in Non-Small Cell Lung Cancer

Abstract: Conclusion: Taken together, the genetic variant of the ERAP1 rs469783 and NCF2 rs10911362 from the MHCI pathway genes may be a promising predictor of survival in NSCLC patients via ERAP1 and NCF2 expression alteration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Differences in the distribution of PD-L1 between the BRAF V600E and non-V600E groups were observed, BRAF V600E expressed more PD-L1 (24). In contrast, Negrao et al showed that the rate of PD-L1 positivity (TPS ≥1%) in the V600E genotype (75.4%) was higher than that in non-V600E genotypes (55.8%) (25). Regarding the results of immunotherapy, the median PFS and OS of the non-V600E BRAF population were 5.4 months and 14.9 months, respectively (25).…”
Section: Discussionmentioning
confidence: 94%
“…Differences in the distribution of PD-L1 between the BRAF V600E and non-V600E groups were observed, BRAF V600E expressed more PD-L1 (24). In contrast, Negrao et al showed that the rate of PD-L1 positivity (TPS ≥1%) in the V600E genotype (75.4%) was higher than that in non-V600E genotypes (55.8%) (25). Regarding the results of immunotherapy, the median PFS and OS of the non-V600E BRAF population were 5.4 months and 14.9 months, respectively (25).…”
Section: Discussionmentioning
confidence: 94%
“…First, the races of the patients included in our study (all populations were Chinese) and the B-FIRST trial (most populations were White) were different, which may have biased the selection of the bTMB cutoff threshold. Second, patients with EGFR mutations and ALK fusions, which have been shown to be associated with low TMB and low PD-L1 expression, were not excluded from this study (21).…”
Section: Discussionmentioning
confidence: 99%
“…NSCLC with epidermal growth factor receptor (EGFR) mutation, anaplastic lymphoma kinase rearrangements, or ROS1 mutations is currently recognized as a negative predictor of immunotherapy efficacy (40,41). NSCLC patients harboring EGFR mutations benefit less from ICI treatment despite high PD-L1 expression (42). Several studies have shown that PD-L1 expression is regulated by complex mechanisms, including EGFR.…”
Section: Specific Gene Alterationsmentioning
confidence: 99%